E-Learning (Edublogs) Social Media Based: its implementation in teaching learning at Islamic Senior High School Bangkalan - Chairuddin Chairuddin (Jurnal Pengabdian Masyarakat Khatulistiwa, 2019)
At present, the application of internet technology in the field of education is very much needed in order to improve the quality and equitable education services. One of them in improving the quality of education is from educators (teachers). The teacher has a very crucial role in the process of teaching and learning. Therefore, the teacher must be able to provide an appropriate method and method so that the classroom atmosphere in PBM becomes enjoyable. The specific purpose of this service is that they are able to understand and properly apply e-learning based learning media. The implementation is held for 2 (two) days, namely: first, the implementation of observation and the introduction process. Then the next day a workshop held on the application of e-learning based  learning media. The result of this dedication is that teachers can apply e-learning based learning models in the teaching and learning process.